Analisis Hubungan Total Resistance dan Kemiringan Jalan Terhadap Konsumsi Bahan Bakar Dump Truck Hino 500 FM 260 JD pada Kegiatan Penambangan Bauksit di PT. Bhakti Karya Mandiri Site Teraju, Kabupaten Sanggau, Provinsi Kalimantan - Akbar Wahyu Pratama; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Bhakti Karya Mandiri (PT. BKM) is a contractor company engaged in bauxite mining. In mining activities, the company uses mechanical tools, namely the Hino 500 FM 260 JD dump truck and the Kobelco SK 330 excavator. The use of these mechanical devices cannot be separated from the use of fuel. The actual consumption of fuel for transportation vehicles in the field in April 2019 was 14,632 liters / hour, this value exceeds the standard fuel consumption for transportation means of 13 liters / hour. One of the factors that affect fuel consumption is road conditions. In general, the maximum slope of roads that can be traversed properly by means of transportation, both up and down on hills, is 8% or 4.5˚. However, the reality in the field is that there are 14 road segments that exceed the maximum standard. Based on the calculation, the relationship between road slope and total resistance to fuel consumption when the dump truck is loaded is based on multiple regression analysis with the equation Y = 0.32412 + 0.01404 X1 + 0.00001851 X2. While the relationship between road slope and total resistance to fuel consumption when the dump truck is empty is based on multiple regression analysis with the equation Y = 0.089 + 0.00305 X1 + 0.00001983 X2.Keyword: Bauxite, Fuel Consumption, Total Resistance, Road Slope, Multiple Regression Analysis